ANTIBIOTIC RESISTANCE PATTERNS OF URINARY TRACT INFECTIONS IN A NORTHEASTERN BRAZILIAN CAPITAL - Mirella Alves CUNHA; Gabriela Lins Medeiros ASSUNÇÃO; Iara Marques MEDEIROS; Marise Reis FREITAS (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Urinary tract infection is a common problem worldwide. Its clinical characteristics and susceptibility rates of bacteria are important in determining the treatment of choice and its duration. This study assessed the frequency and susceptibility to antimicrobials of uropathogens isolated from community-acquired urinary tract infections in the city of Natal, Rio Grande do Norte State capital, northeastern Brazil, from 2007 to 2010. A total of 1,082 positive samples were evaluated; E. coli was the most prevalent pathogen (60.4%). With respect to the uropathogens susceptibility rates, the resistance of enterobacteria to ciprofloxacin and sulfamethoxazole-trimethoprim was 24.4% and 50.6%, respectively. Susceptibility was over 90% for nitrofurantoin, aminoglycosides and third-generation cephalosporins. High resistance rates of uropathogens to quinolones and sulfamethoxazole-trimethoprim draws attention to the choice of these drugs on empirical treatments, especially in patients with pyelonephritis. Given the increased resistance of community bacteria to antimicrobials, local knowledge of susceptibility rates of uropathogens is essential for therapeutic decision making regarding patients with urinary tract infections.